Islamic Guidelines for Digital Commerce: Fatwa MUI No. 146 and its Impact on Indonesia’s E-Commerce Ecosystem - Syahruddin, Aqmar; Mubarak, Husni; Ahmad, Kamaluddin (MUI Sulawesi Selatan, 2024)
This study aims to explore the impact of Fatwa MUI No. 146 on Sharia-compliant e-commerce transactions in Indonesia, particularly focusing on its economic, legal, and social implications. With the rapid growth of online shopping, this fatwa seeks to address challenges such as fraud, transparency, and the alignment of digital transactions with Islamic principles. The research employs a qualitative approach, combining literature review, field observation, and surveys of online shoppers in Indonesia. Data were analyzed to evaluate the extent to which the fatwa has shaped business practices and consumer behavior in the digital economy. The results indicate that Fatwa MUI No. 146 has significantly contributed to the development of a more ethical and transparent online shopping environment by emphasizing key Sharia principles such as trust, justice, and clarity in contracts. It has particularly enhanced the confidence of Muslim consumers and provided guidelines for small and medium enterprises (SMEs) to access broader markets. The fatwa's role in supporting the digital economy is evident, although challenges remain in educating stakeholders about Sharia-compliant business practices. This study is original in its examination of the intersection between Islamic law and digital commerce, contributing to the discourse on Sharia-compliant e-commerce in Indonesia. Its implications are significant for policymakers, religious authorities, and digital businesses, as it suggests the need for stronger collaboration to promote inclusive and fair digital economic practices in accordance with Islamic values.